The relationship between vector insect populations, natural enemies, and disease incidence of tungro virus during wet and dry seasons - RUDI TOMSON HUTASOIT; MUHAMMAD JIHAD; LISTIHANI LISTIHANI; DEWA GEDE WIRYANGGA SELANGGA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hutasoit RT, Jihad M, Listihani L, Selangga DGW. 2023. The relationship between vector insect populations, natural enemies, and disease incidence of tungro virus during wet and dry seasons. Biodiversitas 24: 4001-4007. Tungro virus is one of the most prevalent viruses affecting rice plants. The tungro virus is frequently found in rice plantations because its green planthopper vector is always present. This study aimed to determine the relationship between the population density of green planthoppers and its natural enemies with the incidence of tungro disease during the rainy and dry seasons in Lanrang, Sidenreng Rappang, South Sulawesi. The research method employed was field monitoring of the population density of green planthoppers, natural enemies, and the incidence of tungro disease. The presence of the tungro virus was confirmed by the molecular method using RTSV and RTBV-specific primers. The results showed three types of tungro vector insects: Nephotettix virescens, Nephotettix nigropictus, and Recilia dorsalis. Nephotettix virescens was the dominant vector insect, with the highest population in March and August of 101 and 51 individuals, respectively. During the dry season, the high population of the three vector insects in August was followed by a high incidence of tungro disease in September, reaching 29.38%. Symptoms of yellow leaves have been confirmed by molecular methods, which indicated that the infection was caused by RTSV and RTBV, as evidenced by the amplification of DNA bands measuring 787 bp and 1400 bp. Data on the population of vector insects and the incidence of tungro disease indicated the importance of determining the ideal time to plant to avoid the plant's susceptible phase during the peak vector population between March and August. The dominant natural enemies found during the observations included Araneus inustus, Tetragnatha maxillosa, Agriocnemis pygmaea, and Menochilus sexmaculatus. Increasing the population of natural enemies could suppress the population of vector insects.